Strategi Pengembangan Health Tourism Di Yogyakarta - Kartika Fajar Nieamah; Yitno Purwoko (STIE Pariwisata API Yogyakarta, 2021)
Health tourism is a travel activity to get health services. Yogyakarta is one of the provinces that has the potential to develop health tourism. This is seen by Yogyakarta type A hospitals, having 11 5-star hotels that provide spa and fitness. However, currently health tourism has not been widely realized and has not been developed in Yogyakarta. The purpose of this study was to determine the components of health tourism development and to find out the strategy for developing health tourism. This research uses descriptive qualitative method with data collection techniques using in-depth interviews and literature study. The data analysis method used is the SWOT method. The result of this research is that the components of health tourism development are adequate facilities, qualified human resources, professional medical personnel, affordable prices, marketing, and information technology. The strategy in developing health tourism is to increase promotion from both social and print media, provide training to human resources, provide discounts on certain products, make attractive products, health tourism is covered by BPJS, complete health tourism support facilities, build buildings / interesting facilities so that it becomes its main attraction.